Sexual violence against children and adolescents: an analysis of prevalence and associated factors - Miranda, Millena Haline Hermenegildo; Fernandes, Flávia Emília Cavalcante Valença; Melo, Rosana Alves de; Meireles, Raísa Cardoso (Revista da Escola de Enfermagem da USP, 2020)
Objective: To analyze the prevalence and factors associated with sexual violence against children and adolescents in the city of Petrolina/Pernambuco. Method: Ecological study carried out with data from children and adolescents who were victims of sexual violence, collected in the Information System for Notifiable Diseases and analyzed according to descriptive and inferential statistics, with multiple logistic regression. Results: A total of 1,232 cases of sexual violence against children and adolescents were registered, with a prevalence of 30.6%. Sexual violence was more likely to occur among female victims (Odds Ratio = 11.39), in their own home (Odds Ratio = 1.96), and the father was the most likely aggressor (Odds Ratio = 8.97). Alcohol use by the aggressor increased the chance for the outcome (Odds Ratio = 2.26). Conclusion: The prevalence of sexual violence and associated factors point to the need to implement humane practices within a network of health services integrated with other public systems, with the objective of promoting, protecting and defending the rights of children and adolescents.